Grasp of dihydroartemisinin resistance in Indonesia: Focused on genetic polymorphisms and new antimalarial - Wardhani, Bantari WK.; Permana, Yandi (Narra Sains Indonesia, 2023)
The eastern region of Indonesia is endemic to malaria, a tropical parasitic infection that causes significant mortality. The Sustainable Development Goals (SDGs) encompass the global commitment to prevent and eliminate malaria by the end of 2030. Nevertheless, the biggest issue lies in the antimalarial drug resistance in Indonesia. Genetic polymorphism has been a considerable factor in the mechanism of antimalarial drug resistance of which could lead to inadequate activity of antimalarial drugs to undertake Plasmodium infection by several molecular mechanisms. Hence, first-line therapy for malaria in Indonesia such as dihydroartemisinin, piperaquine, and primaquine, becomes ineffective. However, the resistance is unavoidable. This review aims to summarize the genetic polymorphism possible mechanisms contributing to antimalarial resistance in the Indonesian population and to discuss the potential new antimalarial drug candidates.